Gobierno Digital Y Su Incidencia En Los Procesos Administrativos Del Gad Municipal Del Cantón Buena Fe, Año 2023. - Zamora Rizzo, Alex Adrian (2025)
In the context of public administrations, the implementation of digital government has become a key factor in improving administrative efficiency and the quality of services offered to citizens. Therefore, the general objective of this study is to propose digital transformation strategies to improve the administrative processes of the Municipal GAD of the Canton of Buena Fe by 2023. To gather information about the institution, research methods such as descriptive, explanatory, inductive, deductive, and statistical methods were used, as well as interviews and surveys that facilitated the collection of primary and secondary information, as they helped to understand the reality facing the administrative management of the Municipal GAD of the Buena Fe Canton. The results show that 56.4% of the population believes that the GAD does not facilitate online access to procedures, and more than 65% of internal users believed that the GAD should invest in its technological infrastructure. The Cronbach's alpha test results demonstrated a reliability of 0.944 for the information provided by internal users and 0.869 for external users; this means that there is a correlation between the instruments analyzed. In conclusion, the results demonstrate the urgent need to modernize the Municipal GAD's technological infrastructure to effectively respond to citizen expectations and improve the experience of internal users.